Extension Of Markowitz Model For Portfolio Analysis. - Kamil, Anton Abdulbasah; Kwan, Mei Wan (2004)
This paper focused on portfolio analysis that set-up among 10 selected stocks traded on Kuala Lumpur Stock Exchange (KLSE). Markowitz model is the main method used to build the optimal portfolio for this paper.